2015
DOI: 10.1089/apc.2014.0308
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Enhancing Adherence to Antiretroviral Therapy (ART): A Systematic Review of High Quality Studies

Abstract: We sought to review the effectiveness of interventions designed to improve adherence to antiretroviral therapy (ART) from studies included in a recent Cochrane review that reported a clinical and an adherence outcome, with at least 80% follow-up for 6 months or more. Data were extracted independently and in duplicate, with an adjudicator for disagreements. Risk of bias was assessed using the Cochrane Risk of Bias tool. Of 182 relevant studies in the Cochrane review, 49 were related to ART. Statistical pooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 88 publications
(103 reference statements)
4
53
1
1
Order By: Relevance
“…In other chronic and acute infections, medication adherence is frequently suboptimal and associated with worse clinical outcomes (11)(12)(13). However, there are no studies to date evaluating antibiotic adherence, or the relationship between adherence and clinical outcome, among patients experiencing skin infections.…”
mentioning
confidence: 99%
“…In other chronic and acute infections, medication adherence is frequently suboptimal and associated with worse clinical outcomes (11)(12)(13). However, there are no studies to date evaluating antibiotic adherence, or the relationship between adherence and clinical outcome, among patients experiencing skin infections.…”
mentioning
confidence: 99%
“…The intervention effect for 95% adherence was significantly stronger in studies that used recall periods of 2 or 4 weeks (vs. < 7 days) [26]. Taken together, all the evidence suggests that various ART adherence intervention strategies can be successful, but more research is needed to identify the most efficacious intervention [27]. Recently several studies have looked at the effectiveness of CBT in the improvement of adherence in HIV patients, with or without concomitant depression.…”
Section: Discussionmentioning
confidence: 99%
“…SMS text-based strategies [14] [15], that are not yoked to monitoring but are systematically sent, require a response from participants, and also seem to suggest that an interactive component is particularly beneficial. [16] [17] Garofalo and colleagues recent work in this area with 105 adolescents and young adults where two-way daily SMS texts were provided to non-adherent youth demonstrated a significant improvement in self-reported adherence and high satisfaction scores. [18] Furthermore, a pilot study using personalized, interactive, daily SMS text messages demonstrated significant improvement among 14-to-29 year olds living with HIV with poor self-reported adherence rates.…”
Section: Outreach Between Clinic Visitsmentioning
confidence: 99%